The Effect of Brassica Veggie Spring Roll Recipe Modification on Sensory Evaluation (Color, Aroma, Texture, Taste, Nutritional Value) at Senjani Kitchen Malang - Taqiyya Firdausi Aliyya; Rani Nurmayanti (JURNAL KESMAS DAN GIZI (JKG), 2026)
Recipe modification is the process of creating and developing existing recipes to improve their overall quality. In catering food service, recipe modification aims to enhance menu quality in terms of taste, color, aroma, texture, and nutritional value, making the products more appealing to consumers. Attractive menus are more easily accepted by consumers and can positively influence customer satisfaction. This study aimed to analyze the development of the Brassica Veggie Spring Roll recipe based on sensory evaluation, including color, aroma, texture, taste, and nutritional value, at Senjani Kitchen Malang. The research employed a quasi-experimental method with a posttest-only control group design. The study was conducted in November 2025 at the Integrated Laboratory of Poltekkes Kemenkes Malang. The organoleptic test involved 25 panelists consisting of students from the Applied Bachelor Program in Nutrition and Dietetics and Dietitian Professional students of Poltekkes Kemenkes Malang. The preference assessment scale was categorized into four levels: Strongly Like (SL), Like (L), Dislike (D), and Strongly Dislike (SD). Data were analyzed using univariate analysis with Microsoft Excel and bivariate analysis using the Wilcoxon test. The results showed that the highest hedonic score was found in the aroma of the modified recipe, with a value of 3.52, which fell into the “Like” category. The Wilcoxon test indicated significant differences in preference levels for aroma, texture, and taste (p-value < 0.05), meaning that recipe modification had a significant effect on these attributes. Nutritional value analysis using NutriSurvey 2007 revealed differences in energy, protein, fat, fiber, and carbohydrate content before and after the recipe was modified. Based on these findings, recipe modification influenced aroma, texture, taste, and nutritional value. Future research is recommended to explore color variations in recipe development and to conduct laboratory-based nutritional analysis for more accurate results.